Social Work and Mental Health - Golightley, Malcolm (Exeter : Learning Matters, 2004)
Knowledge of mental health is no longer an option for qualifying social workers, it is an essential requirement for all students. This book will help students to develop skills and understanding that enable them to deliver an appropriate and responsive service for people who face mental health challenges.
Includes bibliographical references (p. 145-153) and index.
Keywords: Social psychiatry; Health and Fitness